Deoxycholic Acid Mitigates Necrotic Enteritis Through Selective Inhibition of Pathobionts and Enrichment of Specific Lactic Acid Bacteria - Melanie A. Whitmore; Jiaqing Guo; Dohyung M. Kim; Jing Liu; Isabel Tobin; Guolong Zhang (Pathogens)
Necrotic enteritis (NE), caused by Clostridium perfringens, poses significant economic challenges to the global poultry industry. The widening ban on in-feed antibiotics in livestock production underscores the need for alternative strategies to combat NE. Deoxycholic acid (DCA), a secondary bile acid, has shown promise in NE mitigation. However, its protective mechanism remains largely unexplored. A total of 120 newly hatched, male Cobb broilers were randomly divided into four treatments to investigate the impact of DCA on host response and intestinal microbiome in both healthy and NE-infected chickens. The results demonstrated that the dietary supplementation of 1.5 g/kg DCA significantly improved animal survival, reversed growth inhibition, and alleviated intestinal lesions (p < 0.01). Furthermore, DCA selectively inhibited the NE-induced proliferation of C. perfringens and other pathobionts such as Escherichia and Enterococcus cecorum. Concurrently, DCA markedly enriched dominant lactic acid bacteria like Lactobacillus johnsonii in both the ileum and cecum of NE-infected chickens. However, DCA had a marginal effect on the jejunal transcriptomic response in both mock- and NE-infected chickens. Therefore, we conclude that DCA protects chicken from NE mainly through the targeted inhibition of pathobionts including C. perfringens, with minimum impact on the host. These findings elucidate the protective mechanisms of DCA, supporting its development as a promising antibiotic alternative for NE mitigation.